Correlation between short-term blood pressure variability parameters with mobil-O-graph pulse wave velocity - Marco Antonio Vieira Silva; Luiz Antonio Pertilli Rodrigues Resende; Mateus Marchiori Vieira; Camila Blanco Ferreira Jajah; Lucas Alves Berzotti; Nicole Cristine Rambourg; Ian Dias de Souza Pierson; João Lucas Carvalho Achkar; Livia Marchiori Vieira; Guilherme Marchiori Moreira; Geisa Ribeiro Borges; Dalmo Correia (BMC, 2022)
Abstract Background Blood pressure variability (BPV) and arterial stiffness show an association with increased cardiovascular events. Evidences demonstrated an association between higher short-term systolic BPV and stiffer arteries. There is no previous study assessed the correlation between BPV and arterial stiffness measured by a Mobil-O-Graph device. We issued to evaluate the correlation between short-term BPV parameters and Mobil-O-Graph pulse wave velocity (PWV) among suspected hypertensive individuals under treatment. Methods Mobil-O-Graph device estimated arterial stiffness (oscillometric PWV [oPWV]) in 649 individuals, and they recorded 24-h ambulatory BP; 428 had suspected hypertension and 221 under treatment. We analyzed the correlation between oPWV and measures of BPV: SD of 24 h BP (24-h SD), SD of daytime BP (daytime-SD), and SD of nighttime BP (nighttime-SD), weighted SD of 24-h BP (wSD), coefficient of variation of 24-h BP (CV 24-h) and average real variability (ARV). Results Oscillometric PWV showed a positive correlation with all systolic BPV measures, in both groups. Among suspected hypertensives: 24-h SD, r = 0.30; SD daytime-SD, r = 0.34; nighttime-SD, r = 0.16; wSD, r = 0.30; CV 24-h, r = 0.24; ARV, r = 0.22. In the treated individuals: 24-h SD, r = 0.46; daytime-SD, r = 0.47; nighttime-SD, r = 0.35; wSD, r = 0.50; CV 24-h, r = 0.43; ARV, r = 0.37, all P < 0.001. Diastolic BPV demonstrated association with some measures of BPV. In suspected hypertensive group: nighttime-SD, r = 0.13; wSD, r = 0.10, both P < 0.001. And in treated individuals: daytime-SD, r = 0.23; wSD, r = 0.22; CV 24-h, r = 0.19 (all P < 0.001), ARV, r = 0.15 (P < 0.05). Systolic daytime-SD in suspected and diastolic CV 24-h in treated group independently predicted oPWV. Conclusion We observed a positive and independent correlation between Mobil-O-Graph pulse wave velocity and BPV measures, strong to systolic BPV and weak to diastolic BP.